2017
DOI: 10.1007/s00430-016-0491-9
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 gene polymorphisms and risk of classic Kaposi’s sarcoma among Iranian patients

Abstract: A single-nucleotide polymorphism (SNP) in the promoter region of MDM2 (SNP309T>G, rs2279744) has been shown to increase the expression of the MDM2 protein in various cancer types. However, only one study has analyzed the role of the MDM2 polymorphism in the development of Kaposi's sarcoma (KS). The association of MDM2 SNP309 with classic KS risk was evaluated in 79 Iranian patients with classic KS and 123 healthy controls. The MDM2 SNP309 was genotyped using PCR and restriction fragment length polymorphism met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Some studies have shown that MDM2 amplification occurs in GC, with an expected impact on p53 pathways (12,13). Furthermore, similar to what has been described for other types of cancer (14)(15)(16)(17)(18)(19), MDM2 polymorphisms that can lead to differential protein activity may have an impact on GC susceptibility (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 56%
“…Some studies have shown that MDM2 amplification occurs in GC, with an expected impact on p53 pathways (12,13). Furthermore, similar to what has been described for other types of cancer (14)(15)(16)(17)(18)(19), MDM2 polymorphisms that can lead to differential protein activity may have an impact on GC susceptibility (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 56%
“…and other types of cancer, such as endometrial, 44 bladder, 45 esophageal squamous cell, 41 Kaposi's sarcoma, 56 and uterine leiomyomas. 43 However, in several studies, an association has been reported between the SNP309 polymorphism and the incidence of BC worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Zhao et al (2012) in a meta‐analysis reported no significant correlation between the MDM2 ‐SNP309 and the incidence of BC in the European populations 12 . A negative association has been confirmed between the MDM2 ‐SNP309 and other types of cancer, such as endometrial, 44 bladder, 45 esophageal squamous cell, 41 Kaposi's sarcoma, 56 and uterine leiomyomas 43 . However, in several studies, an association has been reported between the SNP309 polymorphism and the incidence of BC worldwide 10,11,14,18,23,57‐59 …”
Section: Discussionmentioning
confidence: 99%
“…Risk of classic KS is threefold higher in men from the South of Italy than the North 35 . Transplant recipients of Mediterranean, Jewish and Middle Eastern ancestry (at risk for classic KS) are also overrepresented among iatrogenic KS patients regardless of their residence at the time of the transplant 19,35,36 . Among HIV‐positive patients, risk of developing AIDS‐KS is reported to be higher in South Africa than in Europe, North America and Latin America and the trend of decreased risk concomitant with increased CD4 count after initiation of ART evident in these regions was not observed in South Africa 22 .…”
Section: Evidence For the Existence Of A Genetic Linkmentioning
confidence: 99%
“…35 Transplant recipients of Mediterranean, Jewish and Middle Eastern ancestry (at risk for classic KS) are also overrepresented among iatrogenic KS patients regardless of their residence at the time of the transplant. 19,35,36 Among HIV-positive patients, risk of developing AIDS-KS is reported to be higher in South Africa than in Europe, North America and Latin America and the trend of decreased risk concomitant with increased CD4 count after initiation of ART evident in these regions was not observed in South Africa. 22 Geographic and population-specific prevalence of KSHV and incidence of KS suggest a potential role for host genetic factors in susceptibility to KSHV infection and subsequent development of KS.…”
Section: Evidence For the Existence Of A Genetic Linkmentioning
confidence: 99%